Advancing adaptive facades for a sustainable future in building design - Kadhim, Batool Mowafaq; Maamory, Abdulla S. AL; Ghaban, Ahmed M. AL (Edelweiss Applied Science and Technology, 2025)
The essential need to mitigate carbon emissions has brought the energy performance of the building sector into focus. Conventional static façades, which are unable to adapt to dynamic external conditions, often compromise energy efficiency and occupant comfort. In contrast, adaptive façades present a groundbreaking opportunity to transform building design by responding dynamically to environmental stimuli, optimizing energy consumption, and enhancing indoor conditions. This paper explores the recent advancements in adaptive façade systems, emphasizing their potential to improve thermal comfort, daylight performance, and most essential the energy efficiency. In addition, this paper highlights the transformative role of quantum energy and smart materials in advancing façade performance and sustainable design. Overall, this paper underscores the potential of using adaptive façades to transform sustainable building practices, offering architects, researchers, and designers a roadmap for integrating innovative and energy-efficient solutions into the built environment.